Use of conventional electrochemical techniques to produce crystalline FeRh alloys induced by Ag seed layer - Noce, R. D. [UNESP]; Benedetti, Assis Vicente [UNESP]; Passamani, E. C.; Kumar, H.; Cornejo, D. R.; Magnani, M. (Elsevier, 2013)
By combining galvanic displacement and electrodeposition techniques, an ordered Fe20Rh80 structure deposited onto brass was investigated by X-ray diffractometry, Mössbauer spectroscopy and magnetization measurements. Mössbauer and X-ray diffraction analyses suggest that the Fe-Rh alloy directly electrodeposited onto brass displays a nanocrystalline state while a similar alloy deposited onto Ag/brass shows a faced centered cubic-like structure, with dendrites-like features. These results directly indicate that the presence of Ag seed layer is responsible for the Fe-Rh alloy crystallization process. In addition, room temperature Mössbauer data indicate firstly paramagnetic states for two Fe-species. In the dominant Fe-species (major fraction of the Mössbauer spectra), Fe atoms are situated at a cubic environment and it can be attributed to the γ-Fe20Rh80 alloy based on their hyperfine parameters. In the second species, Fe atoms are placed in a non-local symmetry, which can be related to Fe atoms at the grain boundaries or/and Fe small clusters. These Fe-clusters are in superparamagnetic state at room temperature, but they may be ordered below 45 K, as suggested by magnetization data. © 2013 Elsevier B.V. All rights reserved.
Keywords: Ag seed layer; Electrodeposition; FeRh alloys; Galvanic displacement; Ag seed layers; Electrochemical techniques; Electrodeposition technique; Fe-Rh alloy; Magnetization measurements; Ssbauer spectroscopies; Superparamagnetic state; Atoms; Brass; Deposits; Grain boundaries; Iron alloys; Magnetization; Molybdenum; Rhodium; Silver alloys; Superparamagnetism; X ray diffraction; X ray diffraction analysis; Nanocrystalline alloys